Oral health-related taboos and oral health status among a South Indian Tribal population: A descriptive study - Vikram Simha Bommireddy (Wolters Kluwer Medknow Publications, 2023)
Introduction: Health being a biological and social entity makes an important contribution to economic progress. Though we live in the 21st century still many underserved communities are lacking to adopt healthy lifestyles. One of many reasons would be religious convictions such as taboos, myths, or misbeliefs. Aim: This study aims to assess the periodontal status, and to comprehend the myths and misconceptions among adults in Jeelugumilli Mandala, West Godavari district, Andhra Pradesh. Materials and Methods: A cross-sectional study design was used among 12 panchayats in which 29 villages were present in Jeelugumilli Mandal. Out of 29 villages one village was selected by convenience sampling as it is a manageable unit which represents rural population. Oral examination was done using community periodontal index (CPI) and loss of attachment for those individuals who met inclusion criteria. A valid questionnaire was used to quantitate about social myths and taboos. Pearson's Chi-Square and descriptive statistics were applied to the collected data and level of significance was set at P ≤ 0.05 for the tests. Results: A statistically significant difference was observed in CPI scores among males and females (P = 0.024), those who brush their teeth once daily and those who brush twice (P = 0.005) and high significance was seen among those who consume alcohol and those who do not (P < 0.001). For loss of attachment scores high significant difference was found among tobacco chewers and nonchewers, those who brush once daily and twice daily (P < 0.001). Conclusion: Most of the misbeliefs were seen among illiterates and rural population. Hence, there is a need to improve the level of education as well as knowledge related to health, among these groups for overall improvement of health related quality of life.